Introducing an n-type electron deceleration layer to enhance the luminous efficiency of AlGaN-based DUV-LEDs - Wang, Qiao; Zhang, Kang; Lin, Dan; Liang, Xihui; Liu, Yunzhou; Zhang, Shan; Wu, Hualong; Zhao, Wei (Frontiers in Physics, 2023)
The internal quantum efficiency (IQE) of conventional AlGaN-based deep-ultraviolet (DUV) light-emitting diodes (LEDs) is seriously limited by the poor and inhomogeneous carrier injection. The typical solution is to optimize the structure parameters of p-type region and active region. In this work, however, we try to address this issue by introducing an n-type electron deceleration layer (EDL) underneath multiple quantum wells (MQWs). On one hand, the EDL helps to decrease the electron velocity and thus increase the electron capture rate. On the other hand, it can also reduce barrier heights in the band valence and thus enhance the hole transport in the MQWs. As a consequence, the concentrations of electrons and holes in the MQWs were significantly increased, resulting in the enhancement of radiative recombination. Compared to the conventional structure, the DUV-LED structure with an EDL achieves a higher IQE, leading to a 39% improvement in the light output power. It is believed that performing energy-band engineering in n-type region has great application prospects for high-performance DUV-LEDs.